Benefit of Prolonged Dual Antiplatelet Therapy After Implantation of Drug-Eluting Stent for Coronary Bifurcation Lesions: Results From the Coronary Bifurcation Stenting Registry II. (July 2018) - Jang, Woo Jin; Ahn, Sung Gyun; Song, Young Bin; Choi, Seung-Hyuk; Chun, Woo Jung; Oh, Ju Hyeon; Cho, Sung Woo; Kim, Bum Sung; Yoon, Jung Han; Koo, Bon-Kwon; Yu, Cheol Woong; Jang, Yang Soo; et al.
Abstract : Background: Whether prolonged dual antiplatelet therapy (DAPT) improves clinical outcomes after percutaneous coronary intervention for coronary bifurcation lesion is uncertain. Methods and Results: We evaluated 2082 patients who were treated with drug-eluting stent for bifurcation lesions and were event free (no death, myocardial infarction [MI], cerebrovascular accident, stent thrombosis, or any revascularization) at 12 months after the index procedure. Patients were divided into 2 groups: DAPT ≥12-month group (n=1776) and DAPT <12-month group (n=306). Primary outcome was all-cause death or MI. At 4 years after the index procedure, death or MI occurred less frequently in the DAPT ≥12-month group than the DAPT <12-month group (2.8% versus 12.3%; adjusted hazard ratio, 0.21; 95% confidence interval, 0.13–0.35; P <0.001). After propensity score matching, incidence of death or MI was still lower in the DAPT ≥12-month group than the DAPT <12-month group (2.6% versus 12.3%; adjusted hazard ratio, 0.22; 95% confidence interval, 0.12–0.38; P <0.001). In subgroup analysis, the treatment effect of prolonged DAPT was consistent across subgroups regardless of lesion location, stenting technique, or type of used drug-eluting stent. Conclusions: The risk of all-cause death or MI was significantly lower in the ≥12-month DAPT group than the <12-month DAPT group after percutaneous coronary intervention for bifurcation lesion using drug-eluting stent. Our results suggest that prolonged DAPT may improve long-term clinical outcomes after percutaneous coronary intervention for bifurcation lesions. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01642992